Invasive haemodynamic evaluation of the pulmonary circulation in pulmonary hypertension (Swiss Medical Weekly, 2017)
The term pulmonary hypertension refers to a serious condition characterised by high pulmonary vascular pressure, mainly as a consequence of various cardiac and respiratory diseases. Current clinical classification of pulmonary hypertension considers five distinct groups. Transthoracic echocardiography represents the first and most important noninvasive screening tool for estimating the probability of pulmonary hypertension. The diagnostic approach to pulmonary hypertension is supported by a proposed algorithm, which identifies the underlying cause. The definitive diagnosis and classification of pulmonary hypertension requires invasive confirmation of an elevated pulmonary artery mean pressure during a right heart catheterisation at rest. Pulmonary artery wedge pressure assessment has a pivotal role in differentiating precapillary from postcapillary pulmonary hypertension. The correct acquisition and interpretation of invasive pulmonary haemodynamic variables play a central role, not only in confirming the diagnosis but also in prognostication and treatment decision-making. During right heart catheterisation correct zero levelling of the external pressure transducer and pressure tracing readings at end-expiration should be assured. Obese patients and patients with obstructive lung diseases require special attention, given that spontaneous positive end-expiratory intrathoracic pressures are frequently observed. Because pressure and flow determinations with a fluid-filled flow-directed thermodilution catheter are potentially insufficiently precise, it is recommended to average at least three measurements. Acute vasoreactivity testing is indicated only in selected patients. Recent data suggest that invasive pulmonary haemodynamic measurement during exercise may be more sensitive than resting haemodynamics for early diagnosis, for treatment response assessment and for prognostic purposes.